Death abroad: Medico-legal autopsy results of repatriated corpses: A retrospective analysis of cases at the Department of Legal Medicine in Frankfurt am Main. (May 2020) - Holz, F.; Saulich, M.F.; Schröder, A.S.; Birngruber, C.G.; Verhoff, M.A.; Plenzig, S.
Highlights: A medical examination should be sought upon import into the native country. A second autopsy can provide additional findings (even homicide). Dissection of all organs cannot be assumed, even if all body cavities were opened. Professional fixation and fast transport provide the best conditions for an autopsy. Abstract: Introduction: Repatriated corpses may have been autopsied abroad. The aim of the study was to compare the findings from second medico-legal autopsies with those from primary autopsies abroad to spotlight possible implications for the management of repatriated corpses. Material and Methods: All autopsies from a 20-year period at the Institute of Legal Medicine in Frankfurt am Main on repatriated corpses of German citizens were reviewed. The results were compared with the information from the body passports, the protocols of the autopsies in the country of death, and the police files. Results: In total, 151 corpses repatriated from 56 different countries were autopsied. The interval between death and autopsy in Germany was 2–603 days (median: 11 days). 91 of the repatriated corpses (59.5%) had previously been autopsied abroad. Three body cavities had been opened in 78.0% (71/91) of the original autopsies; among them, there were 11 cases (15.5%) with dissection of all organs, as opposed to 7 cases (9.9%) with all organs intact and in situ. Of the previously autopsied corpses, 62.6% were accompanied by a body passport that noted the cause of death. In nearly 75% of these cases, the stated cause of death was compatible with that established at second autopsy. In 5 cases (10.2%), the cause of death established in the second autopsy disagreed with that on the body passport. The most prominent disparity was a cranial gunshot wound rather than the stated fatal fall. Discussion: This analysis of individual cases spotlights the problematics of an uncritical approval of the body passport. In light of the different procedural autopsy standards around the world, the validity of an autopsy abroad is discussed in the context of the second autopsy results. Conclusion: A second external postmortem examination by qualified medical practitioners should be obligatory in all cases of repatriated corpses, with notification of the criminal police in all cases of non-natural or undetermined death. A timely second autopsy is recommended even in cases with previous autopsy abroad.